2022
DOI: 10.3389/fcell.2021.790618
|View full text |Cite
|
Sign up to set email alerts
|

Isothiocyanate From Moringa oleifera Seeds Inhibits the Growth and Migration of Renal Cancer Cells by Regulating the PTP1B-dependent Src/Ras/Raf/ERK Signaling Pathway

Abstract: Moringa oleifera Lam. is a tropical and subtropical plant that has been used for centuries as both food and traditional medicine. 4-[(α-L-Rhamnosyloxy) benzyl] isothiocyanate (MIC-1) is an active substance in M. oleifera, with anti-cancer activity. However, whether MIC-1 exerts anti-renal cancer effects is unknown. Therefore, the aim of the present study was to evaluate the effects of MIC-1 on the growth and migration of renal cell carcinoma (RCC) cells and to identify the putative underlying mechanism. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The effect observed in GB cells was not unexpected, since a previous report demonstrates that in pancreatic ductal adenocarcinoma cells, PTP1B knockdown induces cell cycle arrest in G0/G1 phase with the consequent down-regulation of some cell cycle regulators needed for the G1/S transition such as CDK2, CDK4 and Cyclin D1 [41]. Furthermore, it has also been reported that PTP1B inhibition induces a G2 cell cycle arrest in renal cell carcinoma, pancreatic and hepatic cancer cells [42, 43]. However, the molecular mechanism by which PTP1B regulates cell cycle progression in these cellular models has not been explored.…”
Section: Discussionmentioning
confidence: 92%
“…The effect observed in GB cells was not unexpected, since a previous report demonstrates that in pancreatic ductal adenocarcinoma cells, PTP1B knockdown induces cell cycle arrest in G0/G1 phase with the consequent down-regulation of some cell cycle regulators needed for the G1/S transition such as CDK2, CDK4 and Cyclin D1 [41]. Furthermore, it has also been reported that PTP1B inhibition induces a G2 cell cycle arrest in renal cell carcinoma, pancreatic and hepatic cancer cells [42, 43]. However, the molecular mechanism by which PTP1B regulates cell cycle progression in these cellular models has not been explored.…”
Section: Discussionmentioning
confidence: 92%
“…RCC has been treated with phytochemicals with pharmacological effects, including antioxidant, anti-inflammatory, and antineoplastic characteristics. [ 40 , 41 ]. Kaempferol, a polyphenol belonging to the flavonoid subgroup, exerted antiproliferative and antimetastasis effects in 786-O cells by attenuating metalloproteinase-2 (MMP-2) expression through the downregulation of the Akt and FAK signaling pathways [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The strain was inoculated into the nutrient broth (NB) and cultured at 37°C for 18 h to the logarithmic growth phase. Moringin was obtained from Moringa seeds with reference to a previous method ( Xie et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%